Design and drag force analysis of an autonomous underwater remotely operated vehicles for coral reef health assessment - Rajendran, Pandiyarajan; Alavandar, Srinivasan (Institute of Advanced Engineering and Science, 2026)
This research presents the conception and building of an inexpensive remotely operated vehicle (ROV) system to ease the tasks of underwater inspection and environmental monitoring in areas where the global positioning system (GPS) signal is not available. A Raspberry Pi-based control unit, an inertial measurement unit (IMU), and depth sensors are merged in the system so that simple data acquisition and remote operation can be carried out. ROV hydrodynamic drag and stability for a state of ideal balance and maneuverability were assessed through tests based on preliminary simulations in Fusion 360 and empirical calculations. The ROV is confirmed to be behaving as expected in terms of stability, imaging capabilities, and responsiveness to operator control in the testing that was done in controlled water environments. This paper, the work, and the testing, in fact, present the initial design, but it is a significant step towards the consideration of the possible further embedding of autonomous features “simultaneous localization and mapping (SLAM)-based navigation, doppler velocity log (DVL), light detection and ranging (LiDAR) systems” for completely autonomous underwater guided missions.